Fitness testing of tennis players: How valuable is it? - Fernandez-Fernandez, J.; Ulbricht, A.; Ferrauti, A. (British Journal of Sports Medicine, 2014)
In tennis, sport-specific technical skills are predominant factors, although a complex profile of physical performance factors is also required. The fitness test batteries assist in examining tennis players` capabilities for performance at different levels in the laboratory as well as in the field, in the junior or elite level. While laboratory tests can be, and are, used to evaluate basic performance characteristics of athletes in most individual sports, in a more specific approach, field-based methods are better suited to the demands of complex intermittent sports like tennis. A regular test battery performed at different periods of the year allows to obtain an individual's performance profile, as well as the ability to prescribe individual training interventions. Thus, the aim of the present review was to describe and evaluate the different physical tests recommended and used by practitioners, sports scientists and institutions (national tennis federations).